Conflito agrário e esvaziamento populacional: a disputa do contestado pelo Espírito Santo e Minas Gerais (1930-1970) - Pontes, Walace Tarcisio (2007)
Capixaba and Mineira colonization front, faced each other around the mountains of Aimores (Serra dos Aimorés), eager to start settling the great land extension ahead during the first decades of the 20th century. Minas Gerais agricultural frontier opened its way through a dense and hostile forest while expanding, going over the discontinuous orography which limited its east border. It went towards the sea and confronted the human crowd that was going opposite way. Considering the inaccurate land limits in that area, the government of Espirito Santo and Minas Gerais claimed jurisdiction over the large territory under antagonistic reasons, litigating exhaustively in the court of law, while a great number of migrants were searching unoccupied lands without concerning about political or judicial quarrels, impelling a settlement of the debated zone. The enormous distance form urban areas as well as access difficulties and unstable and incipient social-political structure which characterized the hard life of those who first occupied that land, did not inhibited a fast and unique demographic increase between 1930 and 1960, when the growth of population in “Serra dos Aimores” surpassed the ones registered in the other areas of the country. The existence of conflictive jurisdictions led to a superposition of authorities within the contested zone, debilitating the public government and also strongly stating the difficult life of its inhabitants. Although there were various authorities, the prevailing one was the strongest, reason why migrants who looked for a land to support their families were victimized. Within this context, fraudulences, threats, abuses and attacks happened either for killers sent by powerful landowners or State agents fighting against small agricultural workers who had taken possession of the land in the referred zone. This atmosphere of brutality and incertitude reflected emphatically into the occupancy process in that region, which also influenced the following decades towards a rural exodus like any other, concerning our regional historiography.